UNLOCKING iTHE iBLACK iBOX iOF iTHE iMEDIATING iROLE iOF iTEACHERS’ iORGANIZATIONAL iCOMMITMENT iIN iINDONESIAN iCONTEXT - Y.L. Sunardiono, Prof. Dr. Harijono, SU. & Dr.Dyna iRachmawati (International Journal of Research Science and Management, 2020)
The ipurpose iof ithis istudy iwas ito iexamine ithe imediating irole iof iteachers’ iorganizational icommitment iin ithe irelationship ibetween itransformational ileadership iand iinstructional ileadership ion ischool iacademic iperformance. iThe isample ifor ithis istudy iconsisted iof i185 isenior iteachers iin i100 iprivate isenior ihigh ischools iin iSurabaya, iEast iJava, iIndonesia. iThey irated itheir iprincipals’ ileadership istyle iaccording ito ithe iMultifactor iLeadership iQuestionnaire i(Transformational iLeadership), ithe iTeaching iand iLearning iInternational iSurvey i(TALIS) iand iTeacher’s iOrganizational iCommitment. iSchool iacademic iperformance iwas imeasured iby inational iexamination iresult iin iMathematics, iEnglish, iand iBahasa iIndonesia. iHypotheses iwere itested iusing ithe iStructural iEquation iModeling-Partial iLeast iSquare i(SEM-PLS). iResults ifound ithat iteachers' iorganizational icommitment ifully imediate isignificantly ithe irelationship itransformational ileadership iand iinstructional ileadership ion ischool iacademic iperformance. iConclusion, ilimitations iand idirection ifor ifuture iresearch iare ialso ipresented.